Communicate to engage: storytelling, content creation, and promoting the idea of sustainability and intercultural dialogue in travel videoblogs - Maj, Anna (Creativity Studies, 2024)
In the area of digital media narratives, an important communication role is played by influencers who, thanks to original media messages, become creative gatekeepers of specific ideas. Travel videoblogs are often underestimated as pure entertainment, whereas they can be seen as important tools for public discourse creators. The research uses methods of compositional and content analysis, supplemented with narratology and netnography. In the space of popular travel videoblogs, the main ideas promoted include the ideas of sustainable development and intercultural dialogue. Bloggers create and stimulate the existence of online communities, express specific ideas, concepts and worldviews that partly come from the area of scientific discourse, particularly anthropological, cultural and ethical ones. The research highlights the serious public role played by the digital nomads as influencers and new kind of friendly authority and presents case study of successful communication strategies, narrative skills and technical competences of authors. The online travel narratives can be seen as marketing of ideas and thus used as practical tool of communication for institutions, non-governmental organizations and other actors of communication. The paper analyses new material (new genres of communication, new channels, new strategies) and topic of high importance in the context of intercultural conflicts and ecological problems. One of the most influential Polish travel vlogs, Globstory by Kaja Kraska (initiated in August, 2014), serves here as a case study. It was chosen because its content is typical for this genre and because of creative and engaging practices of the vlogger who successfully influences the public and its understanding of specific ideas and problems.